A retrospective clinical analysis of inappropriate Xiangdan Injection use: clinical risk profiling and computational hypothesis generation - Zeng, Ji; Wei, Yougang; Zhang, Jinke; Xu, Yiming (Frontiers in Pharmacology, 2026)
PurposeXiangdan Injection, a traditional Chinese medicine preparation, is extensively utilized in clinical settings. Nevertheless, frequent instances of inappropriate administration pose significant safety concerns. The clinical findings were supplemented with in silico analyses (network pharmacology and molecular docking) to generate hypotheses regarding potential bioactive constituents and molecular pathways.MethodsA retrospective analysis was performed on 100 patients who received Xiangdan Injection at Ma’anshan Hospital of Traditional Chinese Medicine. A focused review was undertaken to assess the rationale for using Xiangdan Injection in these 100 patients. Furthermore, as an exploratory supplement, we employed network pharmacology and molecular docking methods, aiming to generate hypotheses regarding the potential basis of their biological activities.ResultsAn analysis of 100 clinical cases identified four primary patterns of irrational drug use: unclear indications (67.8%), inappropriate solvent selection (16.1%), repeated medication (11.3%), and prolonged treatment duration (4.8%). Exploratory network pharmacology suggested that key metabolites (e.g., luteolin) may target proteins such as AKT1 and PTGS2, and potentially associate with pathways like PI3K/AKT. Molecular docking indicated a potential binding affinity between luteolin and PTGS2, offering a preliminary hypothesis for its pharmacological profile. Furthermore, these metabolites were linked to liver-related processes, suggesting a need for vigilance regarding hepatotoxicity with prolonged use.ConclusionThis study identified the main risk patterns of the irrational clinical use of Xiangdan Injection. The computational part of this study put forward hypotheses that need to be verified by future experiments. We also proposed targeted suggestions for improving the safety of clinical medication use.